Responding to Victims of Human Trafficking in the United States: A Review of Treatment Providers - McBride, Morgan A (2020)
Scholars have made strides to illuminate the scope and nature of human trafficking, but there have been minimal efforts to inform responses to victims. Importantly, if we do not address the issues that made people vulnerable in the first place, then they could be susceptible to re-victimization in the future. It is vital then that treatment agencies are available and engaging in effective practices to maximize recovery efforts. Thus, the current study examined treatment providers in the United States in two stages to determine how they respond to victims of these crimes. In the first stage, a systematic literature review was completed to assess what treatment modalities have been applied or discussed in the broader academic literature. In the second stage, a subsequent search was conducted to locate providers who implemented treatment interventions to victims of human trafficking. The results indicate that there is only one treatment program specifically created to respond to trafficking victims—My Life My Choice. The remaining modalities identified have been adapted to respond to sex trafficking victims and they tend to focus on trauma-informed approaches. Additionally, there are relatively few treatment providers who explicitly treat trafficking victims (N = 21) and most focus on sex trafficking among females. The treatment modalities vary in their primary goals; however, most involve evidence-based approaches to treatment that have been adapted to this population. The findings produced by this analysis are intended to build on the knowledge surrounding the treatment of human trafficking victims